PENGARUH DOSIS PUPUK NPK MAJEMUK SUSULAN SAAT AWAL BERBUNGA (R1) PADA PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (GLYCINE MAX [L.] MERILL) - Pratama, Brian Jonata; Nurmiaty, Yayuk; Nurmauli, Niar (Politeknik Negeri Lampung., 2017)
The research was conducted in February to June 2015 in the District of Rajabasa Raya, Bandar Lampung. Research used design of randomized perfect group design with five dosages of compound NPK fertilizer (16:16:16), i.e., 0, 25, 50, 75 and 100 kg/ha applied at R1 (early Flowering) and repeated three times. Homogeneity was tested with Bartlet and the addition data was tested with Tukey, and analysis of kind (if applicable). Mean separation test used orthogonal polynomial on the level of confident 5%. The results showed that application of compound fertilizer NPK 16:16:16 increases soybean yield (t/ha) and nutrient efficiency. However, NPK applications have no effect on plant height, plant dry weight, number of total branches, number of productive branches, total number of pods, and weight of 100 grains of soybean seeds. Dosing up to 100 kg/ha of NPK compound increase soybean yield but still shows a linear graph Keywords: soybean, early flowering (R1), NPK fertilizer, NPK dose.